Comparative Transcriptomics Suggests Early Modifications by Vintec® in Grapevine Trunk of Hormonal Signaling and Secondary Metabolism Biosynthesis in Response to Phaeomoniella chlamydospora and Phaeoacremonium minimum - Romeo-Oliván, Ana; Chervin, Justine; Breton, Coralie; Lagravère, Thierry; Daydé, Jean; Dumas, Bernard; Jacques, Alban (Frontiers in Microbiology, 2022)
Given their well-known antifungal abilities, species of the genus Trichoderma are of significant interest in modern agriculture. Recent studies have shown that Trichoderma species can induce plant resistance against different phytopathogens. To further extend this line of investigation, we investigate herein the transcriptomic response of grapevine trunk to Vintec®, which is a Trichoderma atroviride SC1-based commercial formulation for biological control of grapevine trunk diseases and which reduces wood colonization. The aim of the study is to understand whether the biocontrol agent Vintec® modifies the trunk response to Phaeoacremonium minimum and Phaeomoniella chlamydospora, which are two esca-associated fungal pathogens. An analysis of transcriptional regulation identifies clusters of co-regulated genes whose transcriptomic reprogramming in response to infection depends on the absence or presence of Vintec®. On one hand, the results show that Vintec® differentially modulates the expression of putative genes involved in hormonal signaling, especially those involved in auxin signaling. On the other hand, most significant gene expression modifications occur among secondary-metabolism-related genes, especially regarding phenylpropanoid metabolism and stilbene biosynthesis. Taken together, these results suggest that the biocontrol agent Vintec® induces wood responses that counteract disease development.